INterrogating historical research on São Paulo State Railways:: Theories, methods and sources - Campos, Cristina (Universidade Estadual de Campinas, UNICAMP, Unidade da Faculdade de Ciências Aplicadas de Limeira-SP, vinculada ao Laboratório de Estudos do Setor Público, LESP, 2022)
The essay reflects on the theoretical contributions, methods, and primary sources in studies on the implementation of railroads in Brazil in the nineteenth century. The reflection is the result of social history research of the transfer of railroad technology carried out in the province of São Paulo, which involved capitalists, rural producers, experts, and public officials to introduce the new technology for the installation and operation of this transport system. About historical sources, the text highlights the challenges faced by researchers to locate the documents, reports, and other papers of the first railroad companies, and indicates the possibilities for studies with the existing documentation. From the materials that are available for research, the possibilities of studies that contemplate aspects of railway technique and technology are indicated.